Influencia de las herramientas tecnológicas de E-Learning en el proceso enseñanza-aprendizaje de los estudiantes de bachillerato de la Unidad Educativa Eugenio Espejo durante el periodo 2021-2022 - Caicedo Jimenez, Mariuxi Nila (2022)
Education is considered as a cultural asset; where educational processes have been adjusted according to the changes that society has experienced. With the arrival of technology, educational institutions have been forced to invest to update their knowledge, develop skills and generate new skills; that today, constitute a determining factor to achieve a quality education, through the use of technological tools. The internet is the cultural medium through which the individual has managed to transgress its scope in the educational field. Hence, the management of e-learning technological tools is presented as an alternative solution, for the improvement of learning, within the classroom. Based on the exposed antecedents, it was proposed as an objective of study, to evaluate the students of the first level of baccalaureate of the computer science career of the "Eugenio Espejo" Educational Unit; about the knowledge they have around the technological tools of e-learning, taking as a sample a population of 44 students, of both sexes and in age ranges; From whose results it was possible to extract, that there is a considerable number of students use electronic devices such as cell phones, zoom platforms and other devices; whose usefulness is reduced to the mere fulfillment of class hours, little participatory interaction and a reduced number of attendees, which denotes a lack of interest, motivation and self-education on the part of those who participate in the teaching-learning processes, in the field of virtual education.